2002
DOI: 10.5551/jat.9.163
|View full text |Cite
|
Sign up to set email alerts
|

Association between Preheparin Serum Lipoprotein Lipase Mass and Acute Myocardial Infarction in Japanese Men

Abstract: A sensitive immunoassay system using a specific monoclonal antibody against lipoprotein lipase (LPL) recently demonstrated the presence of an LPL mass in preheparin serum. We reported that a preheparin serum LPL mass (pre-LPL mass) reflected the level of functioning LPL activity in the whole body and could be deeply involved in the progression of coronary atherosclerosis of stable organic angina pectoris. We examined the relation between the pre-LPL mass and acute myocardial infarction (AMI). We studied 44 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Our data support previous studies 6,[10][11][12] suggesting that s-LpL and t-adiponectin occur at low levels in AMI patients. There was a significant positive correlation between s-LpL and t-adiponectin levels in AMI patients, even though no significant correlation was observed in NCA subjects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data support previous studies 6,[10][11][12] suggesting that s-LpL and t-adiponectin occur at low levels in AMI patients. There was a significant positive correlation between s-LpL and t-adiponectin levels in AMI patients, even though no significant correlation was observed in NCA subjects.…”
Section: Discussionsupporting
confidence: 82%
“…Both t-adiponectin and s-LpL were selected as independent variables for AMI as a subordinate factor. We divided the subjects into three groups based on s-LpL and serum t-adiponectin levels (cut-off levels: s-LpL 40.0 ng/mL; t-adiponectin 4.0 g/mL) 5,6,18,19) and performed multiple logistic regression analysis for AMI as a subordinate factor (Fig. 4).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Hitsumoto et al [40,41] compared pre-heparin LPL mass in men with angiographically determined coronary atherosclerosis versus that in men with normal coronary or healthy men. They found that men with coronary atherosclerosis had significantly lower pre-heparin LPL mass than did men without coronary atherosclerosis or healthy men.…”
Section: The Association Of Pre-heparin Lpl Mass and The Incidence Ofmentioning
confidence: 99%
“…They suggest that serum LPL mass is an independent determinant of incidence [40] or severity [41] of coronary artery disease even after adjustments of a number of metabolic parameters, including serum triglycerides and HDL-C.…”
Section: The Association Of Pre-heparin Lpl Mass and The Incidence Ofmentioning
confidence: 99%
“…Hypercholesterolemia has been established as one of the most important coronary risk factors [23][24][25][26] ; however, the average serum TC or LDL-C concentration in subjects with CAD often appears to be within the normal range in the Japanese population [27][28][29][30] . The present study also indicated that serum TC or LDL-C concentrations were not higher in CAD subjects than in NCA subjects.…”
Section: Significance Of S-7kcho In the Progression Of Coronary Athermentioning
confidence: 99%